ANALISIS KANDUNGAN FOSFOR TERHADAP DAYA DUKUNG PERAIRAN DANAU LUT TAWAR UNTUK BUDIDAYA SISTEM KERAMBA JARING APUNG - Fikri Fachriza; Eri Yusni; Nurmatias Nurmatias (AQUACOASTMARINE, 2016)
Lake Lut Tawar is the one of lake in Aceh province. The waters of Lake Lut Tawar used for agricultural activities, settlements, tourism and fisheries. Specifically for fisheries activities in Lake Lut Tawar, existence of floating net aquaculture increase by time to time. The existence of floating net aquaculture activities affect for water quality through feed waste, feces and dead fish. This study aims to determine how big the carrying capacity the waters of Lake Lut Tawar with floating net system of aquaculture, that is based on the presence of phosphorus using the formula of the Minister of Environment Regulation No. 28 of 2009. The research was conducted in January to Mai 2015, sempel capture location is determined based on the environment setting used purposive sampling method. The results showed quality the waters of Lut Tawar Lake still in the freshwater quality standard of Grade II PP 82 of 2001, and the carrying capacity the waters of Lut Tawar lake with total phosphate 0.1407 mg/L was at 23728.61 tons/year as well as the waters area that could be used for floating net cages measuring 19.291 hectaresKeywords: Carrying Capacity, Floating net, Lake Lut tawar